Muslim-Friendly’s homestay in Malaysia: issues and challenges - Othman, Rashidi; Mohd Latiff, Nur Hanie; Abu Kasim, Siti Zubaidah; Hj. Baharuddin, Zainul Mukrim; Hashim, Khairusy Syakirin Has-Yun (2015)
This research explore the shariah compliant and issues of muslim-friendly homestay in Malaysia. Malaysia is a tourism-based country that offer many experience opportunities to the tourist. One of it is homestay-tourism package. There are many homestay accommodation build up especially in rural area. However, the services and surroundings are not fulfil the Islamic way of live. Most of the homestays offer the guests to stay with the owner’s family member without determine the space limitation between owner and guest. Thus, the implication goes to the maslahah of the user and the family. Therefore, the study indicates the issue to be solved with the shariah way. The issues of a shariah compliant and muslim’s friendly homestay were observed based on the Islamic built environment criteria. Among the issues are Bii’ah (2 issues), salaamah (1 issues), nazhofah (1 issues), and sirriyyah (2 issues). All of the homestays were categorized as moderate in practising the shariah attribute. Some elements were lack due to environmental, social, cultural and privacy destruction. In conclusion, there is a need for host and guest in term of awareness and practicality to comply in the muslim-friendly and shariah compliant homestay ecosystem.